Visa restrictions and economic exchange : an empirical investigation - Han, Jie Chou (2017)
This paper examines the effect of visa restrictions on economic exchange and migration flows. Previous studies have not addressed the endogeneity bias of visa restrictions as a result of reverse causality and omitted variable bias. We deal with the endogeneity bias by instrumenting visa restrictions using their somatic/genetic distance and religious/linguistic similarity. To do this, we construct a novel dataset of visa restrictions covering 38,399 dyads for nearly 200 countries. Our results show that visa restrictions have a small but significant negative effect on FDI. For exports and migration flows, we are unable to establish causality as the instruments violate the exclusion restrictions. Our research suggests that restrictive border policies can have detrimental effects on economic outcomes.